The influence of antibiotic prophylaxis on bacterial resistance in urinary tract infections in children with spina bifida - Zegers, Sebastiaan Hermanus Johannes (BMC Infect Dis, 2017)
BACKGROUND: Bacterial resistance to antibiotics is an increasingly threatening consequence of antimicrobial exposure for many decades now. In urinary tract infections (UTIs), antibiotic prophylaxis (AP) increases bacterial resistance. We studied the resistance patterns of positive urinary cultures in spina bifida children on clean intermittent catheterization, both continuing and stopping AP. METHODS: In a cohort of 176 spina bifida patients, 88 continued and 88 stopped using AP. During 18 months, a fortnightly catheterized urine sample for bacterial pathogens was cultured. UTIs and significant bacteriuria (SBU) were defined as a positive culture with a single species of bacteria, respectively with and without clinical symptoms and leukocyturia. We compared the percentage of resistance to commonly used antibiotics in the isolated bacteria in both groups. RESULTS: In a total of 4917 cultures, 713 (14.5%) had a positive monoculture, 54.3% of which were Escherichia coli. In the group stopping AP, the resistance percentage to antibiotics in UTI / SBU bacteria was lower than in the group remaining on AP, even when excluding the administered prophylaxis. CONCLUSION: Stopping antibiotic prophylaxis for urinary tract infections is associated with reduced bacterial resistance to antibiotics in children with spina bifida. TRIAL REGISTRATION: ISRCTN ISRCTN56278131. Registered 20 December 2005.